2020
DOI: 10.1186/s40644-020-0294-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter arterial chemoembolization combined with simultaneous DynaCT-guided microwave ablation in the treatment of small hepatocellular carcinoma

Abstract: Purpose: To evaluate the method and effectiveness of transcatheter arterial chemoembolization (TACE) combined with simultaneous DynaCT-guided Microwave ablation (MWA) for the treatment of small hepatocellular carcinoma (SHCC). Materials and methods: From June 2015 to May 2017, a total of 28 consecutive patients with SHCC received single treatment of TACE and 23 subjects received a combination treatment of TACE with simultaneous DynaCTguided MWA. Following 1 month of treatment, the tumor response was assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 35 publications
3
26
0
Order By: Relevance
“…The mean PFS was significantly higher in the combined group than TACE and MWA groups (p < 0.001). These results are concurrent with the previous studies [4,12,13,22,4,27,28], which showed improved overall and recurrence-free survival and significantly longer time of tumor progression in patients treated with TACE þ MWA compared with TACE alone. In contrast, Chen et al [19] reported that the combined group (TACE þ MWA) had a better time of tumor progression (p ¼ 0.001); however, no significant difference in overall survival (p ¼ 0.317) was observed.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The mean PFS was significantly higher in the combined group than TACE and MWA groups (p < 0.001). These results are concurrent with the previous studies [4,12,13,22,4,27,28], which showed improved overall and recurrence-free survival and significantly longer time of tumor progression in patients treated with TACE þ MWA compared with TACE alone. In contrast, Chen et al [19] reported that the combined group (TACE þ MWA) had a better time of tumor progression (p ¼ 0.001); however, no significant difference in overall survival (p ¼ 0.317) was observed.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the safety of the procedure, in keeping with the literature [4,16,22,25,28,29], the current study demonstrated that the combined therapy was well-tolerated and did not significantly increase the risk of AEs compared with TACE and MWA alone. Although minor AEs were commonly seen in the combined therapy group, they were transient with prompt recovery.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, its covalent bond with carbon generally has high in vivo kinetic stability. These chemical features, alongside its growing availability, make 18 F an important and attractive radiolabel for an enormous range of potential small molecular radiopharmaceuticals, such as FLT ([ 18 F]-3′-fluoro-3′-deoxythymidine, a nucleoside analogue and cell proliferation marker) [ 21 ]; F-DOPA ([ 18 F]dihydroxyphenylalanine, a dopamine precursor analogue used in neuroendocrine and brain tumours) [ 22 ]; F-MISO ([ 18 F]fluoromisonidazole, a nitroimidazole hypoxia imaging agent) and related nitroimidazole derivatives [ 23 ]; [ 18 F]DCFPyL (a prostate-specific membrane antigen (PSMA) ligand used for prostate cancer imaging) and other 18 F-labelled PSMA ligands [ 24 ]; [ 18 F]fluoroethylcholine [ 25 ] and related tracers for prostate and other tumours; and amino acid analogues such as FET ([ 18 F]fluoroethyltyrosine), [ 26 ] FSPG (3-[ 18 F]fluoropropyl)-L-glutamic acid (glutamate analogue taken up by cells through the system x C− transporter) [ 27 ] and [ 18 F]fluciclovine [ 28 ]; to name but a few (Fig. 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the European Association for the Study of the Liver (EASL) and the American Association for the Study of Liver Diseases (AASLD) also use local ablation as first-line treatment for patients with early HCC who are not eligible for surgical treatments or as a bridge to transplantation. At present, computed tomography (CT)-guided thermal ablation is generally accepted by most clinical centers [ 6 9 ]. However, unenhanced CT cannot clearly demonstrate the boundary of ablated lesions during the ablation process, and multiple uses of contrast agents will undoubtedly increase the burden on the kidneys.…”
Section: Introductionmentioning
confidence: 99%